2016
DOI: 10.19173/irrodl.v17i4.2345
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Biographical Factors on Adult Learner Self-Directedness in an Open Distance Learning Environment

Abstract: <p>This study investigated the relationship between self-directedness (as measured by the Adult Learner Self-Directedness Scale) and biographical factors such as age, race, and gender of adult learners enrolled at a South African open distance learning (ODL) higher education institution. Correlational and inferential statistical analyses were used. A stratified random sample of 1,102 mainly black and female learners participated in the study. The Adult Learner Self-Directedness Scale (ALSDS) identified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Помимо результатов образования, отраженных в отметках, для успешности весьма важна позитивность субъективного восприятия обучения студентом, свидетельствующая об удовлетворении потребностей студентов в познании, в развитии, в достижениях, в признании, в самореализации. К субъективным аспектам успешности относят поведенческую вовлеченность, студенческий прогресс, удовлетворенность студентов, достижение результатов обучения, результаты трудоустройства, личностный рост и развитие [13,14]. Под субъективной образовательной успешностью мы понимаем студенческий опыт вовлеченности и самостоятельности в учебно-профессиональной деятельности, опыт реализации в обучении базовых потребностей, а также позитивное оценочное отношение студента к условиям обучения и к себе как субъекту деятельности и развития.…”
Section: образовательный опыт и субъективная успешностьunclassified
“…Помимо результатов образования, отраженных в отметках, для успешности весьма важна позитивность субъективного восприятия обучения студентом, свидетельствующая об удовлетворении потребностей студентов в познании, в развитии, в достижениях, в признании, в самореализации. К субъективным аспектам успешности относят поведенческую вовлеченность, студенческий прогресс, удовлетворенность студентов, достижение результатов обучения, результаты трудоустройства, личностный рост и развитие [13,14]. Под субъективной образовательной успешностью мы понимаем студенческий опыт вовлеченности и самостоятельности в учебно-профессиональной деятельности, опыт реализации в обучении базовых потребностей, а также позитивное оценочное отношение студента к условиям обучения и к себе как субъекту деятельности и развития.…”
Section: образовательный опыт и субъективная успешностьunclassified
“…Students’ expectations about the difficulty of the course (Bourdeaux and Schoenack 2016 ; Pierrakeas et al 2004 )…”
Section: Approach To the Literature Reviewmentioning
confidence: 99%
“…Possible difficulties encountered include: weaknesses in online teaching infrastructure, information gaps, lack of teacher experience, complex environment at home [25]. In addition, at the beginning of this implementation there was a delay, because everyone needed to ensure health to start learning properly, both physically and psychologically [26] [27]. Based on that, this study will analyze the implementation, the constraints found and the expectation that there will be a distance learning that will be carried out in secondary schools in West Sumatra, Indonesia.…”
Section: Thementioning
confidence: 99%